2022
DOI: 10.1155/2022/6853939
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ROR and miR-125b Predict the Prognosis in Heart Failure Combined Acute Renal Failure

Abstract: Objective. To elucidate the correlation between expression levels of long noncoding RNA (lncRNA) ROR and microRNA-125b (miR-125b) with the prognosis in heart failure (HF) patients combined acute renal failure (ARF). Methods. HF patients combined ARF ( n = 90 ) and healthy controls ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this research, the high expression of SNHG7 was closely associated with the increase in Gensini scores, indicating that SNHG7 might have a relationship with the severity of ACS. The abnormally expression lncRNAs is observed as a predictor for the prognosis of cardiovascular illnesses [ 23 , 24 ]. For instance, lncRNA-Ang362 is correlated with the poor overall outcome of patients with coronary heart disease after PCI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the high expression of SNHG7 was closely associated with the increase in Gensini scores, indicating that SNHG7 might have a relationship with the severity of ACS. The abnormally expression lncRNAs is observed as a predictor for the prognosis of cardiovascular illnesses [ 23 , 24 ]. For instance, lncRNA-Ang362 is correlated with the poor overall outcome of patients with coronary heart disease after PCI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of lncRNAs, miRNAs, and mRNAs are tested to be differentially expressed in the serum of patients with cardiac diseases, nominating them as circulating disease markers (Li et al 2018;Xue et al 2022;Ying et al 2022). Hard-done work of our peers have reported that the aberrant expression of lncRNAs in hypertrophic heart, such as MIAT, RMRP, and Ahit (Zhou et al 2018;Yu et al 2020;…”
Section: Discussionmentioning
confidence: 99%
“…Recently, long noncoding RNAs (lncRNAs) which are identified as nonprotein-coding RNAs with over 200 nucleotides length have been revealed to play pivotal roles in molecular diagnosis and pathogenesis in almost all kinds of diseases including tumorigenesis and metastasis of cancers [3][4][5]. In HSCC, it has been proven that lncRNA HOXA11-AS contributed to the proliferation and migration via sponging and negatively regulation of miR-155 [6].…”
Section: Introductionmentioning
confidence: 99%